GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 15 Nov 2019, 03:07

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

The nth term, t(n), of a certain sequence is defined as t(n) = t(n-1)

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 59070
The nth term, t(n), of a certain sequence is defined as t(n) = t(n-1)  [#permalink]

Show Tags

New post 02 Apr 2018, 01:45
00:00
A
B
C
D
E

Difficulty:

  5% (low)

Question Stats:

81% (01:20) correct 19% (02:37) wrong based on 76 sessions

HideShow timer Statistics

Manager
Manager
avatar
G
Joined: 05 Feb 2016
Posts: 166
Location: India
Concentration: General Management, Marketing
WE: Information Technology (Computer Software)
GMAT ToolKit User CAT Tests
Re: The nth term, t(n), of a certain sequence is defined as t(n) = t(n-1)  [#permalink]

Show Tags

New post 02 Apr 2018, 03:02
Bunuel wrote:
The \(n_{th}\) term, \(t_n\), of a certain sequence is defined as \(t_n = t_{n-1} + 4\). If \(t_1 = -11\), then \(t_{82} =\)

(A) 313
(B) 317
(C) 320
(D) 321
(E) 340



t2=t1+4
t3=t2+4
.
.
t82=t81+4

adding all we get t82=t1+81*4, since t1=-11
t82=313.

option A
Senior SC Moderator
avatar
V
Joined: 22 May 2016
Posts: 3657
The nth term, t(n), of a certain sequence is defined as t(n) = t(n-1)  [#permalink]

Show Tags

New post 02 Apr 2018, 19:42
Bunuel wrote:
The \(n_{th}\) term, \(t_n\), of a certain sequence is defined as \(t_n = t_{n-1} + 4\). If \(t_1 = -11\), then \(t_{82} =\)

(A) 313
(B) 317
(C) 320
(D) 321
(E) 340

This problem looks like a regular arithmetic progression.

The standard equation for AP is usually detectable in questions like this one.

\(t_n = t_{n-1} + 4\)

\(t_1 = -11\)
\(t_2 =(t_{1} + 4)=(-11+4)= -7\)
\(t_3 = t_{2} + 4 = -3\)
\(t_4 = t_{3} + 4 = 1\)

The above is equivalent to . . . (looking for standard arithmetic sequence)

\(t_1 = -11\)
\(t_2 = t_1 + 4 = -7\)
\(t_3 = t_1 + 4 + 4 = -3\)
\(t_4 = t_1 + 4 + 4 + 4 = -1\)

Extrapolate the standard equation of arithmetic sequence.
The number of 4s added is (n - 1)
4 = common difference, d

\(a_n = a_1 + (n-1)d\)

Rewrite:
\(t_n = t_1 + (n-1)4\)
\(t_1\) is -11

Hence
\(t_{82} = -11 + (81*4) =\)
\((-11 + 324) = 313\)

Answer A
_________________
SC Butler has resumed! Get two SC questions to practice, whose links you can find by date, here.

Never doubt that a small group of thoughtful, committed citizens can change the world; indeed, it's the only thing that ever has -- Margaret Mead
GMAT Club Bot
The nth term, t(n), of a certain sequence is defined as t(n) = t(n-1)   [#permalink] 02 Apr 2018, 19:42
Display posts from previous: Sort by

The nth term, t(n), of a certain sequence is defined as t(n) = t(n-1)

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne